Health-related quality of life among liver disorder patients in Northern India - Yashika Chugh; Swati Katoch; Deepshikha Sharma; Pankaj Bahuguna; Ajay Duseja; Manmeet Kaur; Radha Krishan Dhiman; Shankar Prinja (Indian Journal of Community Medicine, 2022)
Objective: The present study aims to determine the health-related quality of life (HRQoL) among liver disorder patients being treated in tertiary care hospital in north India and exploration of factors affecting HRQoL. Methodology: The HRQoL was assessed among 230 patients visiting either the outpatient department (OPD) or those admitted in high dependency unit (HDU) or liver intensive care unit (ICU) using direct measuring tools such as Euro QoL five-dimension questionnaire (EQ-5D) and EQ visual analog scale. Multivariate regression was used to explore the factors influencing HRQoL. Results: Mean EQ-5D scores among chronic hepatitis and compensated cirrhosis patients were 0.639 ± 0.062 and 0.562 ± 0.048, respectively. Among those who were admitted in the ICU or HDU, mean EQ-5D score was 0.295 ± 0.031. At discharge, this score improved significantly to 0.445 ± 0.055 (P < 0.001). The multivariate results implied that HRQoL was significantly better among patients with lower literacy level (P = 0.018) and those treated in OPD settings (P < 0.001). Conclusion: HRQoL is impaired among patients suffering from liver disorders specifically those admitted in ICU. Further, there is a need to generate more evidence to explore the impact of determinants and treatment-associated costs on the HRQoL.